Nobiletin Decreases Inflammatory Mediator Expression in Tumor Necrosis Factor-Stimulated Human Periodontal Ligament Cells - Yoshitaka Hosokawa; Ikuko Hosokawa; Kazumi Ozaki (Hindawi Limited, 2021)
Nobiletin, a biologically active substance in the skin of citrus fruits, has been reported to be an effective anti-inflammatory, anticancer, and antimicrobial agent. In this study, we aimed to examine the anti-inflammatory effects of nobiletin on tumor necrosis factor- (TNF-) stimulated human periodontal ligament cells (HPDLCs). Our results demonstrated that nobiletin treatment could decrease the expressions of inflammatory cytokines (C-X-C motif chemokine ligand (CXCL)10, C-C motif chemokine ligand (CCL)2, and interleukin- (IL-) 8), matrix metalloproteinases (MMPs) (MMP1 and MMP3), and prostaglandin-endoperoxide synthase 2 (PTGS2) in TNF-stimulated HPDLCs. Moreover, we revealed that nobiletin could inhibit the activation of nuclear factor- (NF-) κB and protein kinase B (AKT1) pathways in TNF-stimulated HPDLCs. Furthermore, nobiletin treatment enhanced nuclear factor, erythroid 2 like 2 (NFE2L2) and heme oxygenase 1 (HMOX1) expressions in TNF-stimulated HPDLCs. In conclusion, these findings suggest that nobiletin can inhibit inflammatory responses in TNF-stimulated HPDLCs by inhibiting NF-κB and AKT1 activations and upregulating the NFE2L2 and HMOX1 expression.